2019
DOI: 10.1002/cre2.277
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical performance with oral function in older women participating in community‐based health exercise programs

Abstract: Objectives This study aimed to clarify the relationship between physical performance and oral function in older women participating in community‐based physical and oral exercise programs. Material and methods We included 163 older women (mean age: 77.4 ± 8.6 years) who participated in weekly health programs in Takehara City, Hiroshima Prefecture, Japan, from August to December 2018. Physical fitness was assessed using a handgrip strength test, a timed up and go test, a one‐leg standing time with eyes open test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although physical frailty is associated with impairments in the nutritional status and dietary habits, 49‐51 maintenance of oral health can contribute to the prevention of physical frailty, since the oral cavity is the body's primary organ for nutritional intake. The importance of oral health management in enhancing the general health status of older adults has been emphasised in previous studies 52,53 . In particular, saliva is important not only for maintaining oral health status but also for dietary intake, since it performs various essential functions not only for the prevention of oral diseases by lubricating and buffering but also for taste and digestion in nutrition intake 24,54,55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although physical frailty is associated with impairments in the nutritional status and dietary habits, 49‐51 maintenance of oral health can contribute to the prevention of physical frailty, since the oral cavity is the body's primary organ for nutritional intake. The importance of oral health management in enhancing the general health status of older adults has been emphasised in previous studies 52,53 . In particular, saliva is important not only for maintaining oral health status but also for dietary intake, since it performs various essential functions not only for the prevention of oral diseases by lubricating and buffering but also for taste and digestion in nutrition intake 24,54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of oral health management in enhancing the general health status of older adults has been emphasised in previous studies. 52,53 In particular, saliva is important not only for maintaining oral health status but also for dietary intake, since it performs various essential functions not only for the prevention of oral diseases by lubricating and buffering but also for taste and digestion in nutrition intake. 24,54,55 Previous studies have suggested that nutritional status is associated with physical frailty, 2,3,30 but there was insufficient information on nutrient intake in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Four papers from two studies were excluded during full-text examination due to their cross-sectional designs (Kim et al, 2016;Miyoshi et al, 2019Miyoshi et al, , 2020Miyoshi et al, , 2021. One paper relied on self-reported exercise amount and intensity in a large government data set (Kim et al, 2016) and focused exclusively on stroke survivors in the data set.…”
Section: Discussionmentioning
confidence: 99%
“…There are seven criteria for diagnosis of oral hypofunction proposed by the Japanese Society of Gerodontology: oral cleanness, oral dryness, lip and tongue motor function, tongue pressure (TP), occlusal force, masticatory function and swallowing function. 11 Moreover, previous studies have examined the associations between oral health and sarcopaenia, 12 oral function and sarcopaenia, 13 , 14 , 15 , 16 swallowing muscles and sarcopaenic dysphagia, 17 , 18 oral function and physical performance, 19 , 20 , 21 , 22 , 23 oral function and cognitive function 24 and oral function and polypharmacy. 7 Especially, TP and tongue thickness, which are sensitive markers for oral frailty, decrease with age.…”
Section: Introductionmentioning
confidence: 99%